The Gift of the World: An Introduction to the Theology of Dimitru Staniloe - Plekon, Michael (Cistercian studies quarterly, 2004)
Reviews the book "The Gift of the World: An Introduction to the Theology of Dimitru Staniloe," by Charles Miller.